A Communication Strategy for Cost Transparency to Improve Adherence to Scheduled Visits by Mental Health Patients at Lancang Kuning Hospital in Pekanbaru - Dea Vilia Siswoyo; Kahar Mulyani; Erliany Syaodih (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze the communication strategy of cost transparency in improving the adherence to the visit schedule of psychiatric patients at Lancang Kuning Hospital Pekanbaru. Through a qualitative approach, this study examines how the preparation of structured communication and the application of elements of cost transparency can affect the understanding and compliance behavior of patients' families. The results of the study showed that communication strategies delivered sequentially, ranging from clinical conditions to explanations of actions and cost details, were able to reduce confusion, build trust, and strengthen the quality of interaction between health workers and families. The implementation of six elements of cost transparency such as clarity, accessibility, openness, cost details, room for clarification, and consistency of information has been effective and increased the perception of professionalism and accountability of hospitals. The family's level of understanding of the service process and cost structure is directly evident in their adherence to the visitation schedule and treatment procedures, as adequate understanding decreases anxiety and increases readiness to receive services. This study emphasizes that the integration of structured communication and cost transparency reinforce each other in forming accountable, effective, and comfort-oriented services for patients' families.